A Study on the Strategies for Translating Modern Chinese Essays into English: A case Study of Zhang Peiji’s Selected Modern Chinese Essays - Yan, Yang; Chuanmao, Tian (International Journal of Humanities and Education Development (IJHED), 2020)
Chinese prose has a long history. During this period, various famous artists have created many excellent works. Prose is a very important literature and art form which takes writing as creation and aesthetic object. In ancient Chinese literature, prose just like verses and parallel writings, does not pursue rhyme and sentence pattern. This is prose in a broad sense. And I would like to talk about prose in a narrow sense. In modern Chinese literature, prose refers to a literary genre which is in parallel with poetry, novel and drama. The major characteristics of prose are the sincere feeling and the beautiful language. After May 4th Movement, the social literature form was influenced by the New Culture Movement, a number of splendid writers in our country created a good deal of excellent works of prose. These are the precious treasures of Chinese literature, carrying the Chinese spirit and culture. But it is a pity that academics at home and abroad have done few researches on the modern Chinese essays translation, and the study about it is rare. The research on Chinese prose translation study, however, is far from enough. The Chinese prose translation study has lagged behind the other literary genre study all the time. Mr. Zhang's two series of "Modern Chinese Prose Selection" translations are his classic masterpieces. The selected works are all famous prose of young intellectuals after the May 4th Movement in China. The essays in them are of profound significance and full of characteristics of the times. So this article tries to explore Professor Zhang Peiji's translation art style in combination with prose selection. The fact that Professor Zhang has successfully translated also proves that the Chinese can make a great contribution in the Chinese-English translation career. The author also expects that Chinese scholars and translators will actively participate in the translation career, and to learn from each other's strengths in future translations. Really let Chinese culture go to the world as soon as possible.